2013
DOI: 10.1123/jpah.10.6.889
|View full text |Cite
|
Sign up to set email alerts
|

Prescriptive Medicine: The Importance of Preparing Canadian Medical Students to Counsel Patients Toward Physical Activity

Abstract: Medical students are interested in and receptive to the importance of PA. However, not only is there improvement needed for the more than one-third of medical students who are insufficiently active themselves, but substantial change is needed regarding the vast majority of students' current counseling behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
13
0
3
Order By: Relevance
“…This study highlights that 95.6% (n=281) of UBC Family Medicine residents believe that exercise as a medical intervention will be important in their future practice, which is greater than the 53-79% of Canadian and American medical students who reported relevance of PA prescription to their practice. 24,27,28,[57][58][59] The higher importance of EP in the present study may be attributable to several factors, including that the majority of studies reported to date have been conducted in the medical student population, which by comparison are a relatively undifferentiated cohort. In contrast, FMR have chosen primary care and are generally more interested in prevention than their medical colleagues who have chosen an acute, tertiary care based medical discipline.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This study highlights that 95.6% (n=281) of UBC Family Medicine residents believe that exercise as a medical intervention will be important in their future practice, which is greater than the 53-79% of Canadian and American medical students who reported relevance of PA prescription to their practice. 24,27,28,[57][58][59] The higher importance of EP in the present study may be attributable to several factors, including that the majority of studies reported to date have been conducted in the medical student population, which by comparison are a relatively undifferentiated cohort. In contrast, FMR have chosen primary care and are generally more interested in prevention than their medical colleagues who have chosen an acute, tertiary care based medical discipline.…”
Section: Discussionmentioning
confidence: 83%
“…Physically active physicians and medical students have been reported to provide more PA counselling to patients 28,29,57,63 yet the limited studies of residents in the literature has not upheld this relationship. 60 Our data similarly did not follow the pattern of Active Doctor = Active Patient, which likely reflects the diminished PA levels of residents, rather than the relationship between physicians' health behaviours and counselling practices.…”
Section: Active Doctor = Active Patient?mentioning
confidence: 99%
See 1 more Smart Citation
“…4 In part, this delivery mode has produced dismal results, with less than 5% to 28% of the U.S. population meeting the most basic physical activity public health recommendations, 5,6 despite primary-care providers being keenly aware of the benefits of exercise. [7][8][9][10][11][12][13][14][15][16][17] Physicians routinely cite lack of time, lack of reimbursement, and lack of content expertise as the most salient barriers for not providing more comprehensive services regarding exercise programming. 18 As this may preclude the effectiveness of CMS's IBT program, many leaders of public health and medical organizations have called for the American Medical Association (AMA) to partner with the ACSM to develop a delineated arm of allied healthcare, in which primary care providers can refer for exercise evaluation and prescription.…”
Section: Introductionmentioning
confidence: 99%
“…An online survey (via SurveyMonkey®) was considered an acceptable data collection method and has been utilized in previous health-related studies at Western University (e.g., Ng & Irwin, 2013;Pearson, Irwin, & Morrow, 2013).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%